Ethnobiology in One Health - Quinlan, Marsha B.; Quinlan, Robert J. (Ethnobiology Letters, 2016)
The new One Health concept is, essentially, the ethnobiology of health, addressing the interrelation of human, animal and environmental health. Incited by 2003 outbreaks of animal-borne SARS and avian influenza, One Health’s multidisciplinary perspective complements growing international support for interdisciplinary research and health equity. One Health needs researchers able to integrate social and cultural factors into health-related life science questions.